Efficacy and tolerance of one‐third full dose bacillus Calmette–Guérin maintenance therapy every 3 months or 6 months: Two‐year results of URO‐BCG‐4 multicenter study. (25th September 2014) - Pfister, Christian; Kerkeni, Walid; Rigaud, Jerome; Le Gal, Sophie; Saint, Fabien; Colombel, Marc; Guy, Laurent; Wallerand, Herve; Irani, Jacques; Soulie, Michel; The Cancer Committee of the French Urological Association
<x xml:space="preserve">Abstract</x> Objectives To assess bacillus Calmette–Guérin maintenance treatment schedule for non‐muscle invasive bladder cancer at 2 years, using one‐third of the full dose and fewer instillations every 3 months or 6 months. Methods This was a prospective, randomized, multicenter study. All patients had an intermediate‐ or high‐risk non‐muscle invasive bladder cancer. They received three weekly instillations of one‐third dose bacillus Calmette–Guérin every 6 months (group I) and two weekly instillations every 3 months (group II) during 3 years. In the two schedules we assessed efficacy, tolerance, leukocyturia and prostate‐specific antigen. Results No significant difference was observed between the two groups for recurrence at 6, 12 or 18 months. At 2 years, tumor recurrence was observed in 10.9% and muscle invasion in 2.9% of cases. Bacillus Calmette–Guérin tolerance was comparable – the adverse events score was 0.8 in group I and 1 in group II (P = 0.242). No statistical correlation was observed between the adverse events score over 2 years, either for leukocyturia (P = 0.8891) or prostate‐specific antigen level (P = 0.7155). Leukocyturia level was not significantly associated with tumor recurrence or progression. Conclusion One‐third dose maintenance bacillus Calmette–Guérin is effective with no impact on tumor recurrence or muscle invasion. Furthermore, there seems to be no difference in tumor response or side‐effects between patients receiving two or three maintenance instillations every 3 months or 6 months. In clinical practice, the use of leukocyturia or total prostate‐specific antigen levels do not appear to be useful in predicting bacillus Calmette–Guérin toxicity.